Structural insights into a C2 domain protein specifically found in tardigrades. (28th December 2020) - Fukuda, Yohta; Inoue, Tsuyoshi
Abstract: Some tardigrades can survive extremely desiccated conditions through transition into a state called anhydrobiosis. Anhydrobiotic tardigrades have proteins unique to them and they are thought to be keys to the understanding of unusual desiccation resistance. In fact, previous transcriptome data show that several tardigrade‐specific proteins are significantly upregulated under desiccated conditions. However, their physiological roles and chemical properties have been ambiguous because they show low or no similarity of amino acid sequences to proteins found in other organisms. Here, we report a crystal structure of one of such proteins. This protein shows a β‐sandwich structure composed of 8 β‐strands, three Ca 2+ ‐binding sites, and hydrophobic residues on Ca 2+ ‐binding (CBD) loops, which resemble characteristics of C2 domain proteins. We therefore conveniently describe this protein as tardigrade C2 domain protein (TC2P). Because the C2 domain functions as a Ca 2+ ‐mediated membrane docking module, which is related to signal transduction or membrane trafficking, TC2Ps may play a role in Ca 2+ ‐triggered phenomenon under desiccated situations. Our finding provides not only structural insights into a newly discovered desiccation‐related protein family but also insights into the evolution and diversity of C2 domain proteins. Abstract : PDB Code(s): 7DF2 ;